Synergy of cultural and economic communication within the social context of society - Amalia Putri, Riza Qori; Ana Sopia, (Technium Social Sciences Journal, 2026)
This study examines the synergy between cultural communication and economic activities within the social context of society, focusing on two prominent cultural heritage sites in Indonesia the Vredeburg Fort Museum in Yogyakarta and Borobudur Temple in Magelang. Using a descriptive qualitative method with a case study approach, data were collected through observation, interviews, documentation, and literature review. The findings reveal that cultural communication in tourism operates not only through verbal interactions but also symbolically through artifacts, spatial settings, and traditional expressions. Economic activities such as trade, tourism services, and creative industries function as mediums for cultural value exchange while simultaneously generating economic benefits for local communities. Local actors serve as cultural brokers who preserve, interpret, and convey cultural meanings to visitors. The study concludes that economic activities, when grounded in local wisdom and managed sustainably, can reinforce cultural continuity instead of undermining authenticity. The synergy between culture and economy contributes to community welfare, cultural sustainability, and the strengthening of social identity.